Dynamic Analysis of the Stock Price Index and the Exchange Rate Using Vector Autoregression (VAR): An Empirical Study of the Jakarta Stock Exchange, 2001-2004 - Novita, Mila; Nachrowi, Nachrowi D. (Institute for Economic and Social Research, 2005)
.